Comprehensive and Validated Computational Investigations of Structural Integrity, Aerodynamic Behavior, and Its Turbulence Characteristics on Agricultural Drone with and without Payload Devices - Beena Stanislaus Arputharaj; Shyam Sundar Jayakumar; Senthil Kumar Solaiappan; Vijayanandh Raja; Parvathy Rajendran; Maheswari Krishnamoorthy; Hari Prasath Jeyaraj; Senthil Kumar Madasamy; Ragavendra Thaiyan Rajendran; Ali Mahmood Ahmed (Journal of Engineering)
In recent years, multirotor unmanned aerial vehicles (MRUAVs) have seen increased investment and deployment for various novel uses, including intruder surveillance, agro farming, and crack detection in severe environments. An identical line of inquiry motivates this work, which aims to better use MRUAVs for agriculture. This study used an agricultural drone (AD) with a coaxial propeller. The proposed AD has increased stability compared to conventional ADs due to employing a coaxial rotor instead of one of the conventional rotors. The proposed AD can be customized to accommodate a wide range of design requirements; however, this investigation uses a payload weight of 2.5 kg. The coaxial propeller arrangement, the “Y” frame, and the fertilizer tank are among the many complex AD parts built efficiently with the help of the cutting-edge tool CATIA. Predictions of flow behavior over the AD and its side effects are presented to confirm the built AD further. Eddy formation and the subsequent pressure drag developments on the AD are simulated using the province computational tool Ansys Fluent. Velocity profiles of fluid variations over the AD are studied after estimating vertical takeoff, vertical landing, and forward speed conditions for various flexible payloads equipped with MRUAV models. The AD’s minor influence allows the construction of eddy structures within and around it. Finally, AD’s structural displacements and failure factors under aerodynamic loads are commuted through the fluid-structure interaction approach. The suggested agricultural drone, thus, is robust and well suited for multicomputational tool agricultural applications.